2014
DOI: 10.1136/bmjopen-2013-004732
|View full text |Cite
|
Sign up to set email alerts
|

Scales for predicting risk following self-harm: an observational study in 32 hospitals in England

Abstract: ObjectiveTo investigate the extent to which risk scales were used for the assessment of self-harm by emergency department clinicians and mental health staff, and to examine the association between the use of a risk scale and measures of service quality and repeat self-harm within 6 months.DesignObservational study.SettingA stratified random sample of 32 hospitals in England.Participants6442 individuals presenting with self-harm to 32 hospital services during a 3-month period between 2010 and 2011.Outcomes21-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 29 publications
5
90
0
Order By: Relevance
“…Although two‐thirds of clinicians surveyed are using suicide risk assessment tools to assess for risk, there is a wide variation in the type of tools being used. This concurs with prior research that found little consistency in suicide risk assessment practice following‐self harm in hospitals in England . Of the emergency departments sampled in the current research that had more than one respondent within the same department, almost half disagreed as to whether the use of a suicide risk assessment tool was a requirement or not.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although two‐thirds of clinicians surveyed are using suicide risk assessment tools to assess for risk, there is a wide variation in the type of tools being used. This concurs with prior research that found little consistency in suicide risk assessment practice following‐self harm in hospitals in England . Of the emergency departments sampled in the current research that had more than one respondent within the same department, almost half disagreed as to whether the use of a suicide risk assessment tool was a requirement or not.…”
Section: Discussionsupporting
confidence: 85%
“…Five surveys were sent to each participating emergency department between March and September 2016 to allow multiple clinicians in one department to complete the survey. The survey was developed based on prior research and examined: demographic information; whether participants currently use a suicide risk assessment tool in their workplace, and to list them if applicable; whether this was a requirement in their workplace; and whether they would assess a child or adolescent differently to an adult.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, subsequent research from this multicentre study based on individual level data has shown that receiving an assessment may have a protective effect and reduce the likelihood of repeated self-harm [20], although a recent systematic review using aggregate data from studies from a range of countries suggests less positive evidence for the effectiveness of psychosocial assessment [6], but evidence for the thoroughness of assessment and type of aftercare provided was not available. Cooper and colleagues [21] found that there are significant variations in assessment practices and a recent study in the UK demonstrated a significant lack of consensus of the most effective risk assessment to be employed as part of the psychosocial assessment for self-harm [22]. The third implication is that a range of clinical services will be required by many self-harm patients given the multiple and complex problems they are facing.…”
Section: Discussionmentioning
confidence: 99%
“…In a representative sample of hospitals in England, it was the most commonly used scale. 66 A recent systematic review showed that only three studies have examined its ability to predict suicide outcomes, and none of these found it to be predictive. 67 The PPV of the SAD PERSONS scale to predict repeat self harm in emergency department patients at six months was 5%, and its sensitivity for predicting suicide at one year follow-up was 23%.…”
Section: Sad Persons Scalementioning
confidence: 99%